1983
DOI: 10.1152/ajprenal.1983.244.3.f270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostacyclin on short-circuit current and water flow in the toad urinary bladder

Abstract: The effects of prostaglandins of the E series on sodium and water transport have been studied extensively. PGE2 has been shown to inhibit the increase in osmotic water flow produced by vasopressin and to stimulate short-circuit current (SCC) in the toad bladder. On the other hand, the effects of prostacyclin (PGI2), an arachidonic acid product, on sodium and water transport have not been extensively evaluated. The present studies describe the effects of PGI2 on basal and vasopressin-stimulated osmotic water fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…and Natov et al [7] included healthy control subjects. According to animal studies PGI 2 has a direct effect on The present study showed that prostacyclin infusion increased renal plasma flow, the plasma level of ANP, ANG II, and tubular water and sodium handling [1][2][3]. However, it is generally assumed that especially the prostaglandin E HR in healthy control subjects.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…and Natov et al [7] included healthy control subjects. According to animal studies PGI 2 has a direct effect on The present study showed that prostacyclin infusion increased renal plasma flow, the plasma level of ANP, ANG II, and tubular water and sodium handling [1][2][3]. However, it is generally assumed that especially the prostaglandin E HR in healthy control subjects.…”
Section: Discussionmentioning
confidence: 44%
“…Some during PGI 2 infusion. Also, to our knowledge no information exists about the interaction between PGI 2 on the one hand affect the vascular bed, while others have their main effects on the renal tubular handling of sodium and water [1][2][3].The and renal haemodynamics, vasoactive and sodium and water regulating hormones on the other hand in healthy control prostaglandin analogue prostacyclin (PGI 2 ) has been shown to affect both renal and systemic haemodynamics in humans subjects. Therefore we have investigated the acute effect of [4][5][6][7], although the information is ambiguous regarding the effect on renal tubular handling of sodium and water.…”
mentioning
confidence: 99%
“…Our results also suggest the presence of a functional "P site" in the mammalian cortical collecting tubule. Thus, DDA, a known P site agonist (Londos & Wolff, 1977;Londos et al, 1980Londos et al, , 1983Daly, 1982;Pohlman, Yates, Needleman & Klahr, 1983), inhibited the Jv and Lp response to AVP. Inhibition of AVP-stimulated Jv and Lp was observed when DDA was given both prior to and following AVP exposure.…”
Section: Discussionmentioning
confidence: 93%